2016
DOI: 10.1080/15384101.2016.1160972
|View full text |Cite
|
Sign up to set email alerts
|

ABCE1 is essential for S phase progression in human cells

Abstract: ABCE1 is a highly conserved protein universally present in eukaryotes and archaea, which is crucial for the viability of different organisms. First identified as RNase L inhibitor, ABCE1 is currently recognized as an essential translation factor involved in several stages of eukaryotic translation and ribosome biogenesis. The nature of vital functions of ABCE1, however, remains unexplained. Here, we study the role of ABCE1 in human cell proliferation and its possible connection to translation. We show that ABC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…Since NMD is dependent on active translation ( 78 , 79 ), we next examined whether ABCE1 depletion might inhibit NMD indirectly by causing a global translation inhibition. Notably, a previous study has reported that ABCE1 KD in human cells reduces the general translation level ( 80 ). To assess the overall translation activity in control and ABCE1 KD cells, we pulse-chased HeLa cells with puromycin and detected puromycylated nascent polypeptide chains using an antibody against puromycin (Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Since NMD is dependent on active translation ( 78 , 79 ), we next examined whether ABCE1 depletion might inhibit NMD indirectly by causing a global translation inhibition. Notably, a previous study has reported that ABCE1 KD in human cells reduces the general translation level ( 80 ). To assess the overall translation activity in control and ABCE1 KD cells, we pulse-chased HeLa cells with puromycin and detected puromycylated nascent polypeptide chains using an antibody against puromycin (Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…These data support a requirement for Fe-S cluster biogenesis and ABCE1 in NMD. It has been reported that depletion of ABCE1 globally reduces translation (Toompuu et al, 2016). Because of the dependency of NMD on active translation, this could potentially account for impaired decay of nonsense transcripts in ABCE1-deficient cells.…”
Section: Deficiency Of Fe-s Clustermentioning
confidence: 99%
“…Since NMD is dependent on active translation (Carter et al, 1995;Thermann et al, 1998), we next examined whether ABCE1 depletion might inhibit NMD indirectly by causing a global translation inhibition. Notably, a previous study has reported that ABCE1 KD in human cells reduces the general translation level (Toompuu et al, 2016). To assess the overall translation activity in control and ABCE1 KD cells, we pulse-chased HeLa cells with puromycin and detected puromycylated nascent polypeptide chains using an antibody against puromycin (Fig.…”
Section: Nmd Sensitive Mrnas Are Strongly Associated With Polysomes Imentioning
confidence: 99%